Jump-land characteristics and muscle strength development in young athletes - Barber-Westin, S. D.; Noyes, F. R.; Galloway, M. (The American Journal of Sports Medicine, 2006)
Background: Many authors have speculated that altered neuromuscular control and strength of the lower extremity are responsible for the gender disparity in knee ligament injury rates.